Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Temperature‐Related Effects on Disease Susceptibility and Immune Response in Redband Trout ( Oncorhynchus mykiss gairdneri ) Following Challenge With Flavobacterium columnare - Joshua P. Egan; Jie Ma; Veronica L. Myrsell; Zhongqi Chen; Jonathan Masingale; Christopher C. Caudill; Timothy Boyle; Julianna Browning; Shawn R. Narum; Kenneth D. Cain; Paul A. Hohenlohe (Journal of Fish Diseases, 2025)
Heat stress can increase disease risk in fishes by reducing immune function. Interactions between redband trout ( Oncorhynchus mykiss gairdneri ) and Flavobacterium columnare , a causative agent of columnaris disease, provide an opportunity to investigate the effects of temperature on immune function and disease resistance during periods of thermal stress. We conducted three trials to characterise differences in immune function and mortality between redband trout held at 18°C and 21°C following challenge with F . columnare . In trial 1, cumulative per cent mortality (CPM) was low and not statistically different between 18°C and 21°C. In trials 2 and 2, we administered higher challenge doses and observed increased CPM overall and significantly greater CPM at 21°C than 18°C. Redband trout upregulated il‐8 , tnf‐α , igm and igt following infection by F . columnare , suggesting that all of these genes may be involved in immune responses to F . columnare infection. We found no differences in the strength of the immune responses between fish held at 21°C versus 18°C. This indicated that 21°C did not elicit sufficient thermal stress to impair immune function and that increased CPM at 21°C versus 18°C was due to enhanced F . columnare virulence.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Population genetics of estuary and reservoir populations of Harris mud crabs, Rhithropanopeus harrisii, in Texas and Oklahoma - Timothy S. Huebner; Terrence M. Boyle; Russell S. Pfau (Biological Invasions, 2021)

Characterisation of an Australian fowlpox virus carrying a near-full-length provirus of reticuloendotheliosis virus - Subir Sarker; Ajani Athukorala; Timothy R. Bowden; David B. Boyle (Archives of Virology, 2021)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Applications of Geosynthetics to Irrigation, Drainage and Agriculture - Eric Blond; Stan Boyle; Marianna Ferrara; Bruno Herlin; Herve Plusquellec; Pietro Rimoldi; Timothy Stark (Irrigation and Drainage, 2019)
Geosynthetics are man‐made products manufactured to meet specific functions in earthworks and geotechnical projects, such as dams, levees, canals, dikes and other structures commonly found in agricultural engineering. Thanks to the Memorandum of Understanding between the International Geosynthetics Society (IGS) and the International Commission on Irrigation and Drainage (ICID), collaborative efforts are being undertaken to generate awareness of geosynthetics in agriculture. In the Workshop on ‘Applications of geosynthetics to irrigation, drainage and agriculture’ held at the 23rd International Congress of the ICID in Mexico City on 8 October 2017, a group of delegates from the IGS contributed with a series of presentations introducing various functions and applications of geosynthetics. The authors gave an overview of how geosynthetic products are designed and tested to ensure they will fulfil their intended function, focusing on applications to irrigation, drainage and agriculture. A few key considerations were identified as being critical to ensure proper performance of geosynthetic materials, in geotechnical projects in general and in agriculture in particular. The present paper is intended to provide a summary of these presentations. © 2018 John Wiley & Sons, Ltd.

Home range and movement patterns of the Redlip Parrotfish (Scarus rubroviolaceus) in Hawaii - Kathrine G. Howard; Jeremy T. Claisse; Timothy B. Clark; Kelly Boyle; James D. Parrish (Marine Biology, 2013)

Latitudinal patterns of range size and species richness of New World woody plants - Michael D. Weiser; Brian J. Enquist; Brad Boyle; Timothy J. Killeen; Peter M. Jørgensen; Gustavo Fonseca; Michael D. Jennings; Andrew J. Kerkhoff; Thomas E. Lacher Jr; Abel Monteagudo; M. Percy Núñez Vargas; Oliver L. Phillips; et al. (Global Ecology and Biogeography, 2007)
Aim Relationships between range size and species richness are contentious, yet they are key to testing the various hypotheses that attempt to explain latitudinal diversity gradients. Our goal is to utilize the largest data set yet compiled for New World woody plant biogeography to describe and assess these relationships between species richness and range size. Location North and South America. Methods We estimated the latitudinal extent of 12,980 species of woody plants (trees, shrubs, lianas). From these estimates we quantified latitudinal patterns of species richness and range size. We compared our observations with expectations derived from two null models. Results Peak richness and the smallest‐ and largest‐ranged species are generally found close to the equator. In contrast to prominent diversity hypotheses: (1) mean latitudinal extent of tropical species is greater than expected; (2) latitudinal extent appears to be decoupled from species richness across New World latitudes, with abrupt transitions across subtropical latitudes; and (3) mean latitudinal extents show equatorial and north temperate peaks and subtropical minima. Our results suggest that patterns of range size and richness appear to be influenced by three broadly overlapping biotic domains (biotic provinces) for New World woody plants. Main conclusions Hypotheses that assume a direct relationship between range size and species richness may explain richness patterns within these domains, but cannot explain gradients in richness across the New World.

SNPs in the neural cell adhesion molecule 1 gene (NCAM1) may be associated with human neural tube defects - Kristen L. Deak; Abee L. Boyles; Heather C. Etchevers; Elizabeth C. Melvin; Deborah G. Siegel; Felicia L. Graham; Susan H. Slifer; David S. Enterline; Timothy M. George; Michel Vekemans; David McClay; Alexander G. Bassuk; et al. (Human Genetics, 2005)